SENAM AEROBIC EXERCISER CHI MACHINE LEBIH EFEKTIF DARIPADA BERSEPEDA STATIS MENURUNKAN KADAR GULA DARAH PADA PASIEN DIABETES MELLITUS TIPE II DI PUSKESMAS MENGWI III - I Wayan Surasta; Ketut Tirtayasa; I Putu Gede Adiatmika (Program Studi Magister Fisiologi Keolahragaan, Fakultas Kedokteran, Universitas Udayana, 2013)
Diabetes mellitus is a metabolic syndrome with hyperglycemic in characteristic. Exercise is one of intervention hopefully curing diabetes mellitus. The objective of the study was to analyze effect of aerobic exerciser chi- machine and static bicycle reducing of blood glucose level type 2 diabetes mellitus. Design of study quasi eksperiment, pre test and post test control group design. Group 1 (10 samples) was provided aerobic exercise chi-machine and group 2 (10 samples) static bicycle 15 minutes three time a week the duration of six weeks. Study locati was at Mengwi III Public Health Center, of Badung Regency with 20 samples was selected by using simple random sampling from the patient of diabetes mellitus type 2. Result of study is showed aerobic exerciser chi-machine reduced the mean of blood glucose level of 124 mg%. Static bicycle reduced mean of blood glucose level of 70.4 mg%. Conclusion of study aerobic exercise chi-machine more effective 17% than static bicycle exercise (p: 0,028) for reducing of blood glucose level type 2 diabetes mellitus.